2020
DOI: 10.1038/s41467-020-18180-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chromatin organization and gene expression in T cells identifies functional genes for rheumatoid arthritis

Abstract: Genome-wide association studies have identified genetic variation contributing to complex disease risk. However, assigning causal genes and mechanisms has been more challenging because disease-associated variants are often found in distal regulatory regions with cell-type specific behaviours. Here, we collect ATAC-seq, Hi-C, Capture Hi-C and nuclear RNA-seq data in stimulated CD4+ T cells over 24 h, to identify functional enhancers regulating gene expression. We characterise changes in DNA interaction and acti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 52 publications
5
48
0
Order By: Relevance
“…In the past years, several studies started revisiting the 3D chromatin reorganization upon T cell activation using technologies that allow quantitation on a genome-wide scale. A recent study in human CD4 + reported that upon 24h of TCR activation, about 30% of long-range chromatin interactions undergo significant changes, while compartments or TADs remain unaffected (113). In agreement, another study combining ATAC-seq, in situ Hi-C and RNA-seq in human CD4 + and CD8 + cells before and after in vitro TCR stimulation for 72h, reported only minimal changes in compartmentalization.…”
Section: T Cellssupporting
confidence: 61%
“…In the past years, several studies started revisiting the 3D chromatin reorganization upon T cell activation using technologies that allow quantitation on a genome-wide scale. A recent study in human CD4 + reported that upon 24h of TCR activation, about 30% of long-range chromatin interactions undergo significant changes, while compartments or TADs remain unaffected (113). In agreement, another study combining ATAC-seq, in situ Hi-C and RNA-seq in human CD4 + and CD8 + cells before and after in vitro TCR stimulation for 72h, reported only minimal changes in compartmentalization.…”
Section: T Cellssupporting
confidence: 61%
“…Our CCA analysis shows that by aligning samples using shared structures we were able to identify known cell subtypes and characterise the transcriptome of these subtypes, as well as their response to stimulation. Again, while the effect of stimulation has been shown to be similar between samples in bulk RNA-seq 23 , increased sample numbers would be required to confirm this in scRNA-seq. Despite this, these findings suggest it is possible to directly compare samples with different disease activities, an essential step in studies investigating treatment response.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear translocation of NFκB binds to κB elements in target inflammatory response genes, turning them on 28 . Remodeling of these pathways at the chromatin level represents a key regulatory mechanism of the inflammatory response 29 . In addition to these inflammatory pathways, we identified chromatin remodeling at multiple pathways that mediated T-cell metabolic states and control of the cell cycle..…”
Section: Discussionmentioning
confidence: 99%